Worldly Spirituality. Issue 3 (2015) - Bookless, Dave
<x content-type="archive" xml:space="preserve">Abstract</x> This article concerns a Christian spirituality which involves a cycle of prayerful reflection and engaged action within the world of God's creation. It commends the concept of Theocentrism, a paradigmatic shift in how we see our place within God's world, a via media between the blatant anthropocentrism of contemporary mainstream culture and the idealism of eco-centrism. It offers the paradoxical knowledge of God's hope even when all around appears hopeless, and parables that inspire and inform our imagination.